2015
DOI: 10.18549/pharmpract.2015.03.598
|View full text |Cite
|
Sign up to set email alerts
|

Development, test-retest reliability and validity of the Pharmacy Value-Added Services Questionnaire (PVASQ)

Abstract: Objective:(i) To develop the Pharmacy Value-Added Services Questionnaire (PVASQ) using emerging themes generated from interviews. (ii) To establish reliability and validity of questionnaire instrument.Methods:Using an extended Theory of Planned Behavior as the theoretical model, face-to-face interviews generated salient beliefs of pharmacy value-added services. The PVASQ was constructed initially in English incorporating important themes and later translated into the Malay language with forward and backward tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…We use principal axis factoring with Varimax rotation. The detailed in-depth description and completion of this stage can be found in Tan et al27…”
Section: Methodsmentioning
confidence: 99%
“…We use principal axis factoring with Varimax rotation. The detailed in-depth description and completion of this stage can be found in Tan et al27…”
Section: Methodsmentioning
confidence: 99%
“…42 These studies by Tan and colleagues provide the policy maker with important conclusion regarding the implementation challenges of PVAS in Malaysia. [38][39][40][41] In particular, the results suggest that the influence of peers, friends and family plus the ease of which patients can use the services are the main predictors of adoption intentions. Generally, patient knowledge and their expectations can strengthen the relationship between intentions and cognitive perspectives.…”
Section: Discussion: Current Research and The Latest Findings For Malmentioning
confidence: 93%
“…38 This is followed by the questionnaire development stage where a survey instrument is designed based on the thematic analysis gained from the qualitative stage as mentioned earlier. 39 Finally, the authors perform a final stage quantitative studies to capture the mediating effects of knowledge and expectations on intentions 40 and also to study how total cognitive perspectives (made up of subjective norms, perceived behavioural control and attitudes) can moderate the patient's intentions to adopt PVAS. 41 Generally, the recent qualitative findings generally find that for respondents who are elderly and on chronic medications, the introduction of PVAS greatly benefits their compliance and overall health outcomes.…”
Section: Discussion: Current Research and The Latest Findings For Malmentioning
confidence: 99%
“…Phase 1 conclusions will guide the formulation of research questions. 24 The qualitative study performed by Tan et al (2015) showed conclusively that five main themes emerged as significant predictors of intention which were attitudes, subjective norms, perceived behavioural control, knowledge and expectations in agreement with the TPB. 25 We now have a strong incentive to proceed to Phase 2 of the study.…”
Section: Phase 1: Qualitative Explorationmentioning
confidence: 97%
“…al. 39 Minimum acceptable statistical significance is set the cut-off point of p < 0.05 for all tests.…”
Section: Partial Effects: the Moderating Role Of Knowledge And Expectmentioning
confidence: 99%